2017
DOI: 10.1016/j.lwt.2016.10.049
|View full text |Cite
|
Sign up to set email alerts
|

Identification of peptides released from flaxseed (Linum usitatissimum) protein by Alcalase® hydrolysis: Antioxidant activity

Abstract: In this study, the hydrolysis of a flaxseed protein isolate with Alcalase ® was performed as a strategy to generate antioxidant peptides. A chromatographic separation of the hydrolysate was conducted by RP-HPLC. Both hydrolysate and six collected fractions were subjected to ORAC and FRAP assays to evaluate their antioxidant capacity. The higher antioxidant values were shown by fractions containing predominantly low molecular weight peptides, as it was demonstrated by MALDI analysis. Four peptides were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 34 publications
2
53
0
Order By: Relevance
“…Recently, Chalamaiah and colleagues have suggested that the immunomodulatory activity of food‐derived peptides is more related to length (2–10 residues) and to hydrophobic nature. These findings are consistent with our data, since we have demonstrated in a previous study that 70% of FPH are composed of peptides ranging from 500 to 1500 Da and hydrophobic amino acids represented 34.7% of the total amount of amino acids. Possibly, these properties might increase the solubility of the peptides in lipids, facilitating a better binding of these peptides to receptors on the surface of immune cells that could inhibit proinflammatory responses of immune cells in contact with bacterial components such as LPS.…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…Recently, Chalamaiah and colleagues have suggested that the immunomodulatory activity of food‐derived peptides is more related to length (2–10 residues) and to hydrophobic nature. These findings are consistent with our data, since we have demonstrated in a previous study that 70% of FPH are composed of peptides ranging from 500 to 1500 Da and hydrophobic amino acids represented 34.7% of the total amount of amino acids. Possibly, these properties might increase the solubility of the peptides in lipids, facilitating a better binding of these peptides to receptors on the surface of immune cells that could inhibit proinflammatory responses of immune cells in contact with bacterial components such as LPS.…”
Section: Resultssupporting
confidence: 94%
“…In a previous paper, we indicated that FPH and phr‐FPH are composed mainly of peptides, but only FPH contains SDG and p‐coumaric, caffeic, and ferulic acids . The similarity among inhibitory activities of FPH and phr‐FPH indicates that there was no synergistic effect between peptides and phenolic compounds present in these samples.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The highest percentage of amino acid found in raw silkworm pupae was for glutamic acid (13.49%) and the percentage of glutamic acid increased after enzymatic hydrolysis. Amino acid profiles are an important factor affecting the antioxidant capacity of protein hydrolysate (Silva, Hernández‐Ledesma, Amigo, Netto, & Miralles, ). In the current study, the protein hydrolysate from silkworm pupae contained 3.73%–5.35% histidine, 4.32%–5.00% tyrosine, and 8.08%–8.52% lysine (Table ).…”
Section: Resultsmentioning
confidence: 99%